The protein restriction mimetic Resveratrol is an autophagy inducer stronger than amino acid starvation in ovarian cancer cells. Issue 12 (7th September 2017) - Ferraresi, Alessandra; Titone, Rossella; Follo, Carlo; Castiglioni, Andrea; Chiorino, Giovanna; Dhanasekaran, Danny N.; Isidoro, Ciro
Abstract : The potential benefit of nutrient starvation in the prevention and treatment of cancer is presently under consideration. Resveratrol (RV), a dietary polyphenol acting as a protein (caloric) restriction mimetic, could substitute for amino acid starvation. The effects of starvation and of caloric restriction are mediated, among others, by autophagy, a process that contributes to cell homeostasis by promoting the lysosomal degradation of damaged and redundant self‐constituents. Up‐regulation of autophagy favors cell survival under nutrient shortage situation, and may drive cancer cells into a non‐replicative, dormant state. Both RV and amino acid starvation effectively induced the aminoacid response and autophagy. These processes were associated with inhibition of the mTOR pathway and disruption of the BECLIN1‐BCL‐2 complex. The number of transcripts positively impinging on the autophagy pathway was higher in RV‐treated than in starved cancer cells. Consistent with our data, it appears that RV treatment is more effective than and can substitute for starvation for inducing autophagy in cancer cells. The present findings are clinically relevant because of the potential therapeutic implications.